Perancangan dan Pembuatan E-Commerce pada UD. Jackpot Pancing - Novia Melinda Sungguh; Silvia Rostianingsih; Djoni Haryadi Setiabudi (Jurnal Infra, 2017)
In today’s era, information and communication technology makes it easy for people to get through everything instantly. One of theexample is online shopping. Almost all of the people on this earthhave devices such as laptops, computers and smartphones that are increasingly in demand and increasing every year. With this E-Commerce website for UD. Jackpot Pancing makes it easy for customers, especially for fishing lovers to search and browse products that are being sell without having to come directly to offline sales.This Project is created based on UD. Jackpot Pancing owner's request to efficient the sales system in UD. Jackpot Pancing and facilitate both consumers, employees and owners to see products that are being sell online, facilitate sales transactions, data settings and reports. The system is built using PHP, HTML and MySQL database and Bootstrap framework.Through the research that has been done by the author, then generated an e-commerce application that helps employees in the process of checking the stock of goods and product sales on UD. Jackpot Pancing, facilitate consumers to browse and buy products, and facilitate the owner UD.Jackpot Pancing to view sales report, stock items report and returns report via the internet.